PENGUASAAN PASAR OLEH DISTRIBUTOR LAMPU HANNOCHS DI KOTA PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 5 TAHUN 1999 TENTANG LARANGAN PRAKTIK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT - Rahmadani Rahmadani (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2022)
This writer examines the Study of Market Control by Hannochs Lamp Distributor in Pekanbaru City based on Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. This paper focuses on the practice of market domination carried out by the distributor of Hannochs lamps in Pekanbaru City and the impact on competitor products of Hannochs lamps. From there we can conclude that the form of business activities carried out by the Hannochs lamp distributor is whether it leads to healthy or unhealthy business competition. This type of research can be classified as empirical juridical research in other words is Sociological Research (Society) or it can also be called field research. The source of data used in this research is primary data and in addition to supporting primary data, the authors also need secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The data collection technique in this research is the interview method and literature review, and the collected data is then analyzed to draw conclusions. Based on the results of the study, it can be concluded. First, In Article 17 of Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition, it is explained that business actors are prohibited from exercising control over the production and or marketing of goods and or services which may result in monopolistic practices and unfair business . The market domination exercised by the Hannochs lamp distributor has resulted in monopolistic practices, making it difficult for competing business actors to enter the relevant market with the same product. Second, the existence of market control certainly has an impact on market conditions. In Article 19 of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition, it is explained that business actors are prohibited from carrying out one or several activities, either alone or together with other business actors, resulting in obstructed opportunities for competing business actors to enter the relevant market and resulting in against loss of public interest.